Synthesis, Characterization and Antibacterial Activity of Ciprofl oxacin Loaded Polymer Nanoparticles for Parenteral Application - Margarita Y Simeonova; Dragomir Krystev; Galya Ivanova; Isaac Abrahams; Nely Georgieva; Tsvetelina Angelova (International Journal of Nanomaterials, Nanotechnology and Nanomedicine - Peertechz Publications, 2017)
Different polymerization techniques as particle formation processes for ciprofloxacin-loaded poly (butyl cyanoacrylate) nanoparticles (CfH-PBCN) were evaluated to choose the most appropriate in terms of the resulting nanoparticles characteristics suitable for parenteral administration. The formulations prepared by the selected technique were considered concerning size, size distribution, surface charge, loading efficiency, drug release. The mechanism of drug immobilization was also studied. Emulsion polymerization using 0.1 M HCl as an acidifying medium and Pluronic F68 as an emulsifier was found to be the best technique, leading to nanoparticles with a mean diameter below 300 nm, narrow size distribution, and a high drug payload of between 61-81 %. Analytical techniques (FTIR, GPC, XRD and 1H NMR) are consistent with a strong covalent interaction between the drug and the polymer matrix of the nanoparticles. It is proposed that CfH is involved in the initiation of the polymerization process resulting in a modification of CfH molecule that could reduce its susceptibility to efflux in Gram-positive bacteria and eukaryotic cells. The antimicrobial activity of CfH-PBCN against Bacillus subtilis 3562 and Escherichia coli K12 is similar to that of the free drug and confirms that this activity is largely unaffected by the drug's association with the polymer nanoparticles.